Object fine-grained discrimination as a sensitive cognitive marker of transentorhinal integrity - Emma Delhaye; Gabriel Besson; Mohamed Ali Bahri; Christine Bastin (Communications Biology)
Abstract The transentorhinal cortex (tErC) is one of the first regions affected by Alzheimer’s disease (AD), often showing changes before clinical symptoms appear. Understanding its role in cognition is key to detecting early cognitive impairments in AD. This study tested the hypothesis that the tErC supports fine-grained representations of unique individual objects, sensitively to the granularity of the demanded discrimination, influencing both perceptual and mnemonic functions. We examined the tErC’s role in object versus scene discrimination, using objective (based on a pretrained convolutional neural network, CNN) and subjective (human-rated) measures of visual similarity. Our results show that the structural integrity of the tErC is specifically related to the sensitivity to visual similarity for objects, but not for scenes. Importantly, this relationship depends on how visual similarity is measured: it appears only when using CNN visual similarity measures in perceptual discrimination, and solely when using subjective similarity ratings in mnemonic discrimination. Furthermore, in mnemonic discrimination, object sensitivity to visual similarity was specifically associated with the integrity of tErC-BA36 connectivity, only when similarity was computed from subjective ratings. Altogether, these findings suggest that discrimination sensitivity to object visual similarity may represent a specific marker of tErC integrity after accounting for the type of similarity measured.